Potential-induced degradation of Cu(In, Ga)Se2 can occur by shunting the front i-ZnO and by damaging the p-n junction. (15th January 2022) - Muzzillo, Christopher P.; Terwilliger, Kent; Hacke, Peter; Moutinho, Helio R.; Young, Matthew R.; Glynn, Stephen; Stevens, Bart; Repins, Ingrid L.; Mansfield, Lorelle M.
Highlights: We encapsulate laboratory CIGS cells to study field-relevant PID. K-rich borosilicate glass reduces PID, relative to Na-rich soda-lime glass. Stressing cells at short-circuit leads to faster PID than open-circuit. Front-glass stress shunts the i-ZnO buffer, slowly reducing the FF. Back-glass stress drives Na + into the p-n junction to rapidly degrade VOC and FF. Abstract: In this work we test field-relevant potential-induced degradation (PID) behavior by encapsulating laboratory Cu(In, Ga)Se2 (CIGS) solar cells and applying +1000 V uniformly on the face of the front glass. In this configuration, we find that K-rich borosilicate glass reduces the extent of PID relative to Na-rich soda-lime glass. We also find that the standard testing protocol of stressing cells at short-circuit leads to faster PID than stressing cells at open-circuit. We characterize two types of CIGS PID: The first, front shunting PID, is driven by front-glass stress and occurs when alkali metal cations accumulate in the i-ZnO buffer, where they increase shunt conductance to reduce fill factor. The second, p-n junction PID, results from back-glass stress as alkali metal cations pile up near the CIGS surface/CdS buffer, where they reduce charge carrier concentration, open-circuit voltage, and fill factor to degrade efficiency ∼160 times faster than front shunting PID.